1993
DOI: 10.3109/02656739309061480
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperthermia on bone. II. Heating of bonein vivoand stimulation of bone growth

Abstract: Previous studies in vitro have shown that it is possible to achieve comparable temperature distribution in bone and the adjacent soft tissues, under appropriate experimental conditions. The objective of the present work was to determine the effects of hyperthermia on bone in vivo. In order to obtain direct temperature measurements in bone, catheters were surgically installed on top of and inside the medullary cavity of the femur of normal rabbits. The thighs were irradiated with 915 MHz microwaves for 45 min, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…Hyperthermia therapy has been shown to stimulate bone remodelling and the formation of new bone, thus increasing cortical bone density [44][45][46]. The hyperthermal stimulation (1.5-3.0 C above normal) stimulates the longitudinal and concentric growth of the femur and tibia in growing rats and dogs [47].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperthermia therapy has been shown to stimulate bone remodelling and the formation of new bone, thus increasing cortical bone density [44][45][46]. The hyperthermal stimulation (1.5-3.0 C above normal) stimulates the longitudinal and concentric growth of the femur and tibia in growing rats and dogs [47].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the use of conditioned culture media acquired from heat-treated osteoblasts (incubator heating at 42°C for 1 h) enhanced OCN secretion and mineralization in bone marrow mesenchymal cells (Ye et al 2007). In addition to water bath or incubator heating, the exposure to elevated temperatures in the range of 42.5-44°C following treatment with 915 MHz microwave for 45 min generated new osseous tissue (Leon et al 1993). Taken together, thermal stress conditioning can potentially serve as a positive cue for bone regeneration, which could be employed in combination with other tissue engineering exogenous stimuli such as GFs.…”
Section: Introductionmentioning
confidence: 98%
“…However, the use of microwave for extra-corporeal heating of bone seems feasible. Using a dedicated microwave hyperthermia system, Leon et al systematically examined the effect of microwave hyperthermia on bone both in vitro and in vivo [16,17]. They demonstrated that hyperthermia promoted bone deposition.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that hyperthermia promoted bone deposition. The effect of microwave is mainly induced by the alternating electromagnetic fields, which activates the dipoles in the molecule of the material [16]. The collisions of the molecules cause generation of heat inside the object [53].…”
Section: Discussionmentioning
confidence: 99%